(untitled) (المجلة الدولية للبحوث العلمية, 2024)
Growing applied linguistics research has discussed the upsurge of the usage of Arabic language among Arabic speakers in the United States (Bale, 2010; Sehlaoui, 2008); language contact and conflict among Arab Americans (AAs; Rouchdy, 2002); and how mobility—both virtual and physical—influences their identities (Duff, 2015). This study researches how AAs define their affiliation to the Arabic language in the United States to understand their attitudes on language variety and ethnic diversity, religion and identity, and stereotypes of Arabs. After analyzing interviews, all three AA participants self-selected their identity based on linguistic and physical contexts. Thus, the findings suggest further research on AAs should consider cyberidentity as a factor for bilingual speakers and compare it with Arabic speakers in their home country.